Pengaruh Pemangkasan Cabang Lateral dan Dosis Pupuk NPK terhadap Hasil Tanaman Mentimun (Cucumis sativus L.) Varietas Roberto - Tomasoa, Reni; Rehatta, Herman; Lehalima, Imelda Theresia (Fakultas Pertanian, Universitas Pattimura, 2025)
The purpose of this study was to evaluate how the development and yield of the cucumber plant of the Roberto variety (Cucumis sativus L.) were influenced by the lateral branch pruning method and the application rate of NPK fertilizer. The doses of NPK fertilizer, particularly without fertilizer (D0), 10 g/plant (D1), 20 g/plant (D2), and 30 g/plant (D3), as well as lateral branch pruning methods, i.e., without pruning (P0), pruning at the first to fifth nodes (P1), and pruning at the sixth to tenth nodes (P2), were the treatments evaluated. Factorial design in random block design (RBD) with three replicates was used to conduct the study. The number of plants, height, leaves, male and female flowers, diameter and length of fruits, and weight were among the observation criteria. The number of leaves, the number of male and female flowers, and the diameter of the fruit were all significantly affected by lateral branch pruning, according to the data. In addition, the NPK fertilizer dosage significantly affected the yield and growth of cucumbers on most of the characteristics measured. Yields increase synergistically when pruning and NPK fertilizer dosage are combined. In conclusion, the Roberto cucumber variety can maximize growth and yield by combining lateral branch pruning with the right dosage of NPK fertilizer. Cucumber cultivation techniques can be based on the findings of this study to increase productivity.